(untitled) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
In order to carry out selection processes in Grapefruit cultivation, the starting dates of phenological phases were observed for 3 lemon varieties and 5 mandarin varieties, with the beginning of phenological phases ranging from March 14th to 20th, and flowering starting from April 8th to 24th. The duration of flowering ranged from 12 to 18 days. The second growth period in the varieties started from May 6th and continued until June 20th, with a duration ranging from 23 to 46 days during this phase.